Co-existence of Morgagni's cyst with a twisted vas aberrans and "bell clapper" deformity in a 15-year-old boy: a case report - Athanasios G. Pegios; Apostolos P. Andronikou; Ioannis Ch. Georgakis; George S. Papouis (SpringerOpen, 2023)
Abstract Background The testicular appendix is a residual of the paramesonephric and mesonephric duct, most commonly found close to the superior pole of the epididymis as Morgagni's cyst. Torsion of such cysts is a common event in children, and the patient usually presents with a palpable testis with a tender mass in its upper pole. The co-existence of two or more appendices is very rare. In addition to the fact that Morgagni's cyst was the non-twisted one and vas aberrans was, made clinical and radiological diagnosis difficult. Case presentation Our patient, a 15-year-old boy, presented with persistent pain in the right scrotum, a significant palpable mass accompanied by vomiting. Upon surgical exploration, a large dark cyst was found located on the right side of the right testicle with a 720-degree torsion. The cyst was straightened and excised along with a Morgagni's cyst. The testis was fixed in the right hemiscrotum due to a "bell clapper" deformity that was also a finding. Conclusions Pathological findings were consistent with a twisted cyst of a testicular appendix (vas aberrans). Co-existence of two or more appendices is very rare in addition to the fact that Morgagni's cyst was the non-twisted one. Usually and in very few cases, a second appendix is found randomly, during surgical exploration for acute scrotum due to torsion of Morgagni's cyst.